Putusan Hakim Terhadap Kasus Narkoba Saiful AG Berdasarkan Undang-Undang Narkotika Studi Perkara Putusan 1677/Pid.Sus/2023/PN.Mdn - Juliandi Juliandi; Devany Maulana Nasution; Parlaungan Gabriel Siahaan; Dewi Pika Lbn Batu (Deposisi: Jurnal Publikasi Ilmu Hukum, 2023)
Narcotics are substances or drugs that are very useful, especially in the medical world and are needed to treat certain diseases. However, if it is misused or used not in accordance with treatment standards, it can have very detrimental consequences if accompanied by the abuse and illicit trafficking of narcotics which results in greater danger to the life and cultural values ​​of the nation which will ultimately weaken national resilience. The research method we use is a Case Study research method in which we examine a criminal defendant with methamphetamine as contained in Case Number: 1677/Pid.Sus/2023/PN Mdn, Wednesday 20 September 2023. vIn the case of a methamphetamine drug courier , two perpetrators named Saiful ag and Marzali were caught red-handed carrying 4 kilograms of methamphetamine. For their actions, the two defendants were charged under Article 114 2 of Republic of Indonesia Law Number 35 of 2009 concerning Narcotics or Article 112 Paragraph 2 of Republic of Indonesia Law Number 35 of 2009 concerning Combination Drugs. with Article 55 Paragraph 1 of the Criminal Code